(untitled) (Archive of Conferences, 2021)
"One of the most important conditions for the protection of the independence and territorial integrity of the Republic of Uzbekistan is the education of servicemen loyal to a highly professional, military and patriotic duty," said the President of the Republic of Uzbekistan in August 2018. There are many reasons why military and patriotic education is considered at the level of state duties. There is a saying, "He who does not feed his army feeds another army." Our ancestor Amir Temur said: "A strong army will be a strong state, an army of a strong state will be strong."